Adonis : the art magazine of the male physique. (Jersey City : Adonis Publications.)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : 16, Hopkins Avenue, Jersey City ; vanaf 1958 : 801 Palisade Avenue, Union City, New Jersey
Engels
Periodiek